Implementation Of Restorative Justice As a Solution To Environmental Pollution Due To Hazardous And Toxic Waste Metal Industry In Pesarean Village, Adiwerna District, Tegal Regency - Pratika, Kamillia (UMPurwokerto Law Review, 2022)
Abstract Environmental pollution is stated in Article 1 point 14 of Law Number 32 of 2009 concerning Environmental Protection and Management. In Indonesia, research on environmental pollution has received much attention in recent years, considering its impact. Mainly if this environmental pollution contains hazardous waste such as hazardous and toxic waste materials that cause several kinds of diseases. Pollution and destruction of the environment are detrimental to the people living around it. Of course, the perpetrators of pollution or environmental destruction must account for every act that harms other people. One way of accountability that can be done regarding the environment is by using the Restorative Justice model. Therefore, this paper aims to find out what form of application of restorative justice is as a solution to environmental pollution due to toxic and hazardous waste and what the obstacles are to its implementation. The research method uses a normative juridical approach with secondary data and literature studies and uses qualitative data analysis. Settlement using restorative justice, which is possible, can be applied in law enforcement to tackle environmental crimes, namely resolving conflicts between the parties through kinship Keywords: Environmental Pollution, Restorative Justice and Hazardous, and Toxic Was Abstrak Pencemaran lingkungan tercantum dalam Pasal 1 butir 14 Undang – Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup. Di Indonesia, penelitian yang terkait dengan pencemaran lingkungan telah menjadi perhatian di beberapa tahun terakhir dengan mengingat dampak yang ditimbulkannya. Apalagi jika pencemaran lingkungan ini mengandung limbah yang berbahaya seperti limbah bahan berbahaya dan beracun yang menyebabkan beberapa macam penyakit. Pencemaran dan perusakan lingkungan tentu sangat merugikan masyarakat yang tinggal disekitarnya. Tentunya setiap perbuatan yang merugikan orang lain haruslah dipertanggungjawabkan oleh pelaku pencemaran atau perusakan lingkungan. Salah satu cara pertanggungjawaban yang dapat dilakukan mengenai lingkungan hidup adalah dengan penyelesaian menggunakan model Restorative Justice. Oleh karena itu, tulisan ini bertujuan menemukan seperti apa bentuk penerapan restorative justice sebagai solusi pencemaran lingkungan akibat limbah B3 serta apa saja hambatan dalam penerapannya. Metode penelitian yang menggunakan pendekatan yuridis normative dengan data sekunder dan studi kepustakaan serta menggunakan analisis data secara kualitatif. Penyelesaian menggunakan restorative justice yang dimungkinkan dapat diterapkan dalam penegakan hukum untuk menanggulangi tindak pidana lingkungan hidup yaitu menyelesaian konflik para pihak melalui jalan kekeluargaan Kata kunci: Pencemaran lingkungan, Restorative Justice dan Limbah Bahan Berbahaya